Mad honey (grayanotoxin) poisoning in Ghalegaun, Lamjung, Nepal: a case report - Poudel, Pipul; Khanal, Arpana (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Mad honey, derived from Rhododendron nectar, contains grayanotoxins that can precipitate an acute cholinergic-like toxidrome characterized by bradyarrhythmias, hypersalivation, and sweating. Nepal, particularly Himalayan districts such as Lamjung, has culturally significant wild-honey harvesting and periodic intoxications. We report an adult from Ghalegaun, Lamjung, who developed dizziness, vomiting, hypersalivation, hypotension, and sinus bradycardia within two hours after ingesting locally harvested wild honey for recreational purposes. Symptoms resolved within 48 hours with oxygen, intravenous fluids, ondansetron, and atropine. Recognition of the characteristic symptom cluster (sudden gastrointestinal upset, bradycardia, and hypotension after honey ingestion) enables prompt supportive management and prevents unnecessary investigations. Community education in honey-harvesting regions is warranted